Respuesta :

Answer:

B. 47

Step-by-step explanation:

The formula for an arithmetic sequence is

an = a1+d(n-1)

a1 =3   (it is the first term)

We can find the common difference by taking the second term and subtracting the first term

5-3 =2

d=2

n = the term number we are looking for

an = 3 + 2(n-1)

We are looking for the 23rd term so n=23

a23 = 3 +2(23-1)

      = 3 +2(22)

      = 3+44

      = 47

Answer:

B. 47

Step-by-step explanation:

The sequence goes up by 2 each time, so to find the nth term, start with 2n.

For n = 1, 2n = 2(1) = 2, but we need 3, so modify to 2n + 1.

For n = 1, 2n + 1 = 2(1) + 1 = 2 + 1 = 3

For n = 2, 2n + 1 = 2(2) + 1 = 4 + 1 = 5

For n = 3, 2n + 1 = 2(3) + 1 = 6 + 1 = 7

Try n = 4 and 5, and you will get 9 and 11, respectively.

2n + 1 works for any term n, where n is natural number.

For the 23rd term, n = 23.

2n + 1 = 2(23) + 1 = 46 + 1 = 47

Answer: B. 47